The Effect of Trim on Tanker, Container and Bulk Carrier Ship Toward the Reduction of Ship’s Exhaust Gas Emission - Fadillah, Arif; Undap, Robin (Department of Naval Architecture - Diponegoro University, 2021)
Emission is one of the few environmental problems, and ships are one of the modes of transportation that produce it. This study aims to define the impact of using optimal trim during the cruising phase, so it can decrease the resistance and the fuel consumption, which will lead to less emission produced by the ship. The type and amount of ships used in this study are three tanker ships, three container ships, and two bulk carrier ships. The methodology used in this study is by using Holtrop’s resistance calculation method with the help of Maxsurf software. The resistance, the power needed, and the fuel consumption is calculated on 22 trim variations and seven speed variations. This study determined that the average decrease in fuel consumption caused by trim optimization for tanker, container, and bulk carrier ships is 5.641%, 8.269%, and 15.704%. Furthermore, the average decrease of emissions produced by tanker, container, and bulk carrier is 6.494%, 11.317%, and 13.775%, respectively. These results are narrowed down to conclude that trim optimization can reduce fuel consumption by up to 9.871% and decrease the emission produced by up to 10.529% for the three types of ships used in this study.